AB0637 Haematological involvement of primary sjogren's syndrome patients in a single centre study of 232 chinese cases. (12th June 2018) - Wang, X.; Wu, Z.; Liang, Y.; Cheng, F.; Feng, R.; Fang, X.; Yang, S.; Gong, B.; Tang, J.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a commono systemic autoimmune disease, characterised by lymphocytic infiltration of the secretory glands and different extraglandular manifestations. Besides haematological disorders are prevalent but not well recognised in patients with pSS. Objectives: Our aim is to determine the existence of cytopenia at diagnosis or during follow-up of our pSS patients as well as the associated factors. Methods: A cohort of pSS patients that had been followed-up in the Department of Rheumatology, Tongji hospital of Tongji University, from 2011 to 2017 was retrospectively assessed. Clinical and laboratory findings about the patients were recorded. Results: Out of 232 pSS patients composing the cohort, cytopenia was already present in 55.60% (n=129) at the time of diagnosis. Anaemia was detected in 30.17% (n=70), leukopenia in 37.5% (n=87), neutropenia in 22.41% (n=52), and thrombocytopenia in 26.72% (n=62) of patients. The proportion of patients with cumulative cytopenia was 6.47% (n=15). Cumulative cytopenia was disease-related in 5.60% (n=13) and medication-related in 0.86% (n=2) of the patients. In patients with cytopenia at the time of diagnosis, erythrocyte sedimentation rates (ESR) were higher (p<0.001), C3 and C4 hypocomplementemia was more prevalent (p<0.001, p=0.060), and they were positive for anti-SSB at a greater proportionand (p=0.058). Hyperglobulinemia, C3 hypocomplementemia, positive anti-SSA and anti-SSB might increase the incidence of anaemia in pSS, with OR of 2.700, 2.042, 1.537 and 1.901, respectively. In addition, logistic regression analysis suggest C3 hypocomplementemia might be associated with different types Leukopenia(p<0.01), while abnormal Transaminase and C4 hypocomplementemia are independent risk factors for thrombocytopenia with a OR of 4.171 (1.516–11.480) and 5.697 (1.662–19.523). Cytopenia in pSS patients not either at diagnosis or during follow-up, was always easy to be ameliorated, but several cases leaded to unfavourable outcome. Conclusions: The most common haematological disorders in pSS patients are leukopenia, and cytopenia in pSS patients might be related to disease activity. References: [1] Tim Both, et al. Reviewing primary Sjögren's syndrome: beyond thedryness – From pathophysiology to diagnosis and treatment. Int. J. Med. Sci. 2017, 14(3): 191–200. [2] García-Carrasco M, et al. Serologic features of primary Sjögren's syndrome: Clinical and prognostic correlation. Int J Clin Rheumtol2012;7(6):651–659. Acknowledgements: We would like to thank all of the participants who took part in the studies featured in this research. The present work was sponsored by the National Natural Science Foundation of China (No. 81273295, 81302562, 81671598), China International Medical Exchange Foundation (Z-2014–06–2–1620), and Shanghai Sailing Program (No.17YF1417200). Disclosure of Interest: None declared